2022
DOI: 10.3389/fcimb.2022.834888
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus Persistence in Porcine Tonsils Is Associated With a Weak Induction of the Innate Immune Response, an Absence of IFNγ mRNA Expression, and a Decreased Frequency of CD4+CD8+ Double-Positive T Cells

Abstract: In humans, Japanese encephalitis virus (JEV) causes a devastating neurotropic disease with high mortality, whereas in pigs, the virus only causes mild symptoms. Besides tropism to the central nervous system, JEV seems to harbor a particular tropism for the tonsils in pigs. This secondary lymphoid organ appears to act as a reservoir for the virus, and we show that it is found up to 21 days post infection at high viral titers. The immune response in the tonsils was studied over time upon intradermal inoculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…As previously demonstrated in young piglets [8,50], adult pigs also had JEV persistence in tonsils, lymph nodes, brain, and nasal mucosa collected 28 days after inoculation (S8 Fig).…”
Section: Japanese Encephalitis Virus Persists In the Upper Reproducti...supporting
confidence: 81%
“…As previously demonstrated in young piglets [8,50], adult pigs also had JEV persistence in tonsils, lymph nodes, brain, and nasal mucosa collected 28 days after inoculation (S8 Fig).…”
Section: Japanese Encephalitis Virus Persists In the Upper Reproducti...supporting
confidence: 81%
“…However, the presence of a pig inside the case’s residence strengthened the evidence for the diagnosis of JE, as pigs are its natural amplifying host, while mosquitoes are the vectors to both animals and humans, who are dead-end hosts for JEV. ( 10 )…”
Section: Discussionmentioning
confidence: 99%
“…In response to Mycobacterium tuberculosis infection, peripheral CD4+CD8+DPT cells have both pro-inflammatory and anti-inflammatory effects, expressing more cytolytic markers (CD107a, granzyme B, and perforin), Th1 type cytokines (TNF, IL-2, IFN- γ), Th17 type cytokines, IL-10 ( 59 ). It has been found that peripheral CD4+CD8+DPT cells are likely to play a role in protective immunity in animals ( 60 62 ). In addition, peripheral CD4+CD8+DPT cells express immune memory markers, which can produce rapid Th1 response and cytotoxic response to previously infected or highly replicated persistent infected viruses, antigens, and vaccines ( 58 , 63 ).…”
Section: Discussionmentioning
confidence: 99%